Teachers' Opportunities and Challenges in Facing the Digital Era (A Systematic Literature Review) - Sumiati, Sumiati; Yuni Aminatus Sa’diyah; Andy Prasetyo Wati; Ludi Wishnu Wardana; F. Danardana Murwani (Profesional Muda Cendekia Publishing, 2024)
The development of information technology and these advancements impact human life as a whole, especially in the field of education and for teachers. In the current era of technology, unrestricted by space and time limitations, learning approaches can be student-focused, encouraging creativity and independent learning, and preparing them for global competition. E-learning-based learning provides advantages in the learning culture. Teachers need to continuously develop knowledge, skills, and abilities to facilitate effective learning. The advancement of information technology provides great opportunities and challenges for teachers to improve their competencies. Teacher competencies, including pedagogical, personality, social, and professional aspects, must be continually enhanced to address current global challenges. To face these challenges, teachers need to understand technology trends not lag, and be ready to adapt to changes in information technology.